Developing instructional materials for English learners in the content areas: An illustration of traditional and contemporary materials in science education. Issue 1 (10th August 2022) - Grapin, Scott E.; Haas, Alison; Llosa, Lorena; Lee, Okhee
Abstract : Research on TESOL materials development has focused primarily on instructional materials for contexts in which students are learning English separate from academic content (e.g., science, mathematics). This research could benefit from expansion given the increasing number of contexts in which students are learning content and English language simultaneously. In U.S. K–12 education specifically, a fast‐growing population of English learners (ELs) is expected to achieve academically rigorous content standards that reflect new ways of thinking about content, language, and their integration. Thus, developing instructional materials based on the standards has necessitated shifts from traditional to contemporary approaches. The purpose of this article is to illustrate how instructional materials for ELs in the content areas have evolved over time. After describing conceptual shifts in the fields of content area education and language education that underpin the evolution of instructional materials, the researchers present traditional and contemporary elementary science units. Then, they analyze the units in relation to key features of traditional and contemporary materials for ELs in the content areas. Finally, they discuss how materials development in content learning contexts could expand the scope of TESOL materials development by providing a fresh perspective on ongoing debates and tensions in this vibrant research area.